Three-Dimensional Correction in Patients With Lenke 1 Adolescent Idiopathic Scoliosis: Comparison of Consecutive Versus Interval Pedicle Screw Instrumentation. Issue 2 (January 2016) - Ketenci, Ismail Emre; Yanik, Hakan Serhat; Demiroz, Serdar; Ulusoy, Ayhan; Erdem, Sevki
Abstract : Study Design: A retrospective-matched cohort study. Objective: To assess the correction of the adolescent idiopathic scoliosis (AIS) deformity in three dimensions, comparing consecutive and interval pedicle screw (PS) instrumentation techniques. Summary of Background Data: The number of the sites that should be implanted with pedicle screws in AIS surgery is controversial. Coronal and sagittal planes have been investigated thoroughly but there are very little data about transverse plane correction according to PS density. Methods: A total of 76 AIS patients who underwent posterior fusion with PS instrumentation were recruited in this study. Patients were divided into two groups according to PS density with 38 patients in each group. In group 1, consecutive PS instrumentation was used (CPS group), and in group 2 interval pedicle screw instrumentation (IPS group). Two groups were matched according to similar patient age, fusion levels, curve magnitude and flexibility, identical Lenke curve type, and identical operative methods. Patients were compared at 1-year follow-up according to radiographic changes in coronal, sagittal, and transverse planes. Clinical outcomes were assessed using Scoliosis Research Society-22 and spinal appearance questionnaires. Results: The two cohorts were well matched. At 1-year follow-up, major coronal Cobb angle changes were 45.4° in CPS group and 38.9° in IPS group ( P = 0.049). T5-T12 sagittal Cobb angle changes were 5.1° and 5.9° in CPS and IPS groups, respectively ( P = 0.897). Apical vertebral rotation changes were measured as 12.0° in CPS group and as 3.6° in IPS group, which demonstrated a significant difference ( P = 0.001). Scoliosis Research Society-22 scores were similar in both groups, whereas spinal appearance questionnaire appearance domain was significantly better in CPS group at 1-year follow-up ( P = 0.035). Conclusion: CPS provides better deformity correction in AIS surgery in all three planes, compared with IPS. Improved deformity correction results in better appearance outcomes. Level of Evidence: 3